Alternative Methods of Treatment for Organic Animal Production: A Survey of “Baitarname” (Veterinary Manuscript) - Ali Yiğit; Aşkın Yaşar (Turkish Journal of Agriculture: Food Science and Technology, 2017)
Manuscripts, containing thousands of years of information and experiences about the treatment of diseases of other animal species, mostly horses, are known by different names such as baitarname, esbname, haylname and bazname. These authentic works, which were also established during the Islamic Civilization period, also bear the traces of different civilizations such as Ancient Egypt, Ancient India and Ancient Greek. With this study, it was aimed to shed light on the evaluation of these manuscripts which have thousands of years of knowledge in terms of treatment and preventive medicine in organic animal production. The main material of the work is originated of a manuscript work conducted as a doctoral thesis and of information on the subject. In addition, books, theses, researches and compilation studies that can be reached within the scope of the subject and which were studied before were also evaluated. In these study, it is observed that the use of herbal, animal and mineral resources as medicines in the treatment, as well as the applications of phlebotomization and cauterization are among the treatment methods. Increased pharmacological, toxicological and clinical trials on herbal, animal and mineral drugs, which are accepted as a complementary role even if they are not alternative, could be a valuable source of organic animal production for which artificial drug use is prohibited or restricted.